Cyclonic storm of 14-15August 1974 In the Bay of Bengal –A radar study - BHATTACHARJEE , P.; DE, A. C. (MAUSAM, 1976)
Tracking of the cyclonic storm of 14-15 August 1974 with the help of S-Band radar at Calcutta has been reported in this communication. The rather slow moving storm remained within a radius of 200km from the radar site for about 36 hours thus enabling the radar to track it. The eye of the storm could be seen on the radarscope for more than 24 hr, even 12 hr after crossing of the coast. Saugar Island and Contai, two of the coastal observatories were traversed by the eye of the storm. The radar data were compared with the surface observations recorded at these two stations. The characteristics of the eye of the cyclonic storm, the vertical structure and sector-wise distribution of the associated cloud system and rainfall distribution are discussed.